Espalha que é aula, junta que é livro : o ensino da economia criativa no ambiente digital - Machado , Veronica Bidart de Castro Nelson (2018)
This research analyzes the circulation environment of the creative economy products in the digital universe, in order to propose an innovative active methodology for the classroom. From the concepts of convergence culture, spreadable media and hospitality, a prototype of an active methodology was created that leads students to plan, create, produce and distribute in their social networks the academic content taught by a teacher which has the role of a mentor and curator. At the end of the active methodology process, the student evaluates the result of the airing his messages, through the interaction registered in the metrics of his social networks. The opportunity we perceive is to transform passive teaching into an active process, motivated by the new paths of education in universities and bring the academic sector and the creative sector closer. As a contribution, we have developed a theoretical framework that supports the expansion of academic content for other media as a methodology and shows that it is possible to spread knowledge and gather at the end of the academic journey, the material spread by the networks, in a digital book